Pedometers and participatory school-based health education – an exploratory study. Issue 6 (30th September 2014) - Louisa Bruselius-Jensen, Maria; Danielsen, Dina; Kirstine Viller Hansen, Ane
Abstract : Purpose: – The purpose of this paper is to explore how pedometers (simple gadgets that count steps) can be used as tools in participatory health education to enhance primary school children's insights into, and abilities to reflect on, physical activity in their daily life. The paper focuses on how using pedometers fosters participation and enhances reflection concerning physical activity. Design/methodology/approach: – The paper draws on findings from an exploratory project with sixth-grade classes (12-13 years) in four Danish primary schools. The approach is called Imove. In Imove, pupils use pedometers to study their own patterns of physical activity, transform their data into statistics, and use the statistical representation to reflect on how physical activity is integrated into everyday life patterns, and how different activities constitute an active life. Findings: – The paper concludes that pedometers support pupils' participation in studying their own health practices, and the step data provide new insights into, and encourage pupils to reflect on, the way physical activity is formed into everyday patterns. Research limitations/implications: – The study is an exploratory one with four participating school classes. The findings need to be further explored by employing similar methodology in studies with more participants. Nevertheless, there is no doubt that pedometers support pupils' genuine participation in health educational processes. Practical implications: – The findings identify simple measuring technologies, such as pedometers, as potent assets in health education learning processes and call for creative thinking in developing health promotion programmes for young people. Originality/value: – Measuring technologies play an increasingly critical role in health research, as well as in individual health regulating practices. This paper contributes with a new perspective by demonstrating the educational possibilities of applying pedometers in participatory school health education.